Comparison of Lipid Profiles in Patients with Type 2 Diabetes Mellitus with Good Glycemic Control and Poor Glycemic Control in RSUD Dr. Saiful Anwar Malang - Yudha, Nyoman Satvika Dharma; Arsana, Putu Moda; Rosandi, Rulli (Jurnal Penyakit Dalam Indonesia, 2021)
Introduction. Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to insulin resistance, deficiency of insulin action, or both with a prevalence of 8.5% in Indonesia. Evidence regarding the relationship between HbA1c and lipid profile in type 2 DM is currently contradictory, therefore a study was conducted to examine the relationship between glycemic control and lipid profile for DM patients.Methods. This survey research was conducted at the outpatient endocrine clinic Dr. Saiful Anwar Malang Hospital in 2014-2019 with a total of 1,308 patients. Patients were then classified into type 2 DM patients with good (HbA1c < 7%, n = 291) and poor glycemic control (HbA1c > 7%, n = 1017).Results. There were lower levels of total cholesterol (183.9 (SD 38.7) mg/dl vs. 198.6 (SD 44.8) mg/dl; p < 0.001), triglycerides (144.2 (SD 67.5) mg/dl vs. 172.9 (SD 112) mg/dl; p < 0.001), and low-density lipoprotein (LDL-C) (119.2 (SD 32.1) mg/dl vs. 131 (SD 35.4) mg/dl; p < 0.001) in type 2 DM patients with good glycemic control compared to poor glycemic control group. There was no significant difference in high-density lipoprotein (HDL-C) levels between the two groups (47.7 (SD 13.4) mg/dl vs. 47.5 (SD 12.7) mg/dl; p = 0.89). There was a significant correlation between total cholesterol levels (r = 0.232; p < 0.001), triglycerides (r = 0.223; p < 0.001), and LDL-C (r = 0.20; p < 0.001) with HbA1c levels.173Jurnal Penyakit Dalam Indonesia | Vol. 8, No. 4 | Desember 2021|Perbandingan Profil Lipid pada Pasien Diabetes Melitus Tipe 2 dengan Kontrol Glikemik yang Terkendali dan Kontrol Glikemik yang Tidak Terkendali di RSUD Dr. Saiful Anwar Malang Conclusion. Type 2 DM patients with good glycemic control had significantly lower total cholesterol, triglycerides, and LDL-C levels compared to type 2 DM patients with poor glycemic control.